Tradisi Maulid sebagai Media Dakwah Rahmat perspektif Living Qur’an-Hadis - Mala, Faiqotul; Rahman, Fazlul (Dakwah, 2024)
The friction between tradition and religion has always been a matter of debate. For example, a local community tradition that is still alive and growing today is the celebration of Prophet's Birthday tradition. The ritual, which is carried out with the aim of remembering the Prophet Muhammad SAW, is commemorated every year on the 12th of Rabi'ul Awal. The implementation is packaged in an attractive, lively and even luxurious manner in various places, giving rise to fanaticism in the celebration process. This is what attracts the author to discuss more deeply the study of how the traditional celebration of Maulid is constructed and the public's understanding of the essence of Maulid? How is the shift in the meaning of grace used as a theological argument in the Prophet's Birthday tradition? How to restore the traditional function of Mawlid as a medium for preaching mercy? This article uses an analysis of living Qur'an hadith as a phenomenon that lives in East Java society, especially Lumajang. The approach used is an anthropological approach and the grace (rahmat) paradigm as a perspective in studying the meaning of grace which is used as a postulate in the celebration of the Prophet's birthday. Through this lens of grace, understanding the essence of the Prophet's birthday can actually create a good life. The essence of grace in the Mawlid tradition should continue to be 'revived' so that it can become a medium for preaching to create a friendly and graceful face of Islam. Where the characteristics of a good life are the creation of prosperity, peace and happiness both in this world and the hereafter.